Sri Lanka energy sector assessment, strategy, and road map. - Joshi, Kaushal (Country sector and thematic assessments, 2019)
It outlines ADBs experience and strategy in the countrys energy sector and provides background information about investment and technical assistance operations. The report also reviews previous support from ADB and other development partners.